(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
Ahmad Donish, a prominent 19th-century intellectual from Central Asia, is regarded for his contributions to the region’s Enlightenment movements, advocating for reform and modernization. His ideas, influenced by European Enlightenment thought, emphasized the importance of rationalism, scientific inquiry, secularism, and educational reform. Donish’s works promoted the separation of religion and politics, the modernization of educational curricula, and the inclusion of women in intellectual life. This article explores Donish’s Enlightenment ideas within the broader context of Central Asia’s intellectual history, focusing on his advocacy for social, educational, and economic reforms. It also examines the lasting impact of his ideas on later generations of reformists and their influence on the modernization of Central Asian societies. Ultimately, Donish’s legacy remains significant in understanding the intellectual transitions from traditionalism to modernity in the region.